Methodology of Egyptian Inheritance Law Reform - Khitam, Husnul; Hayati, Siti Muna; Rahmawati, Anif; Utsany, Royan (KALOSARA: Family Law Review, 2025)
Studies on Islamic inheritance law in Egypt have thus far tended to be descriptive-historical, particularly concerning the codification through Law No. 77 of 1943 and Law No. 71 of 1946, without offering much critical assessment of the methodological foundations of takhayyur (cross-madhhab selection), taṭbīq (contextual application), and tajdīd (reinterpretation). This gap highlights the lack of theoretical reconstruction regarding the state’s institutional ijtihād and the limited analysis of the reform’s impact on society, gender justice, and cross-national inheritance dynamics. This study aims to analyze the methodological construction of Egypt’s inheritance law reforms, evaluate their implications for the principle of substantive justice, and examine their relevance to contemporary challenges. Theoretically, it employs the concept of institutional ijtihād—namely the role of the state in selecting and adapting the opinions of fuqahāʾ—to explain the flexibility of Islamic law within the modern legal order. The findings indicate a significant redefinition, including: restricting homicide as an impediment to inheritance solely to cases of intentional killing; granting equal rights in al-masʾalah al-mushtarakah; expanding radd rights for widowers/widows; introducing special regulations on lineage acknowledgment (al-muqarr lahu bi al-nasab); and the establishment of the obligatory will (waṣiyyah wājibah) for orphaned grandchildren. These results affirm that Egypt’s inheritance law reform represents an effort to balance classical fiqh with modern social demands. The implication is that the Egyptian model may serve as a reference for other Muslim-majority countries, including Indonesia, in formulating inheritance law that is more just, adaptive, and oriented toward gender justice and legal pluralism.   Keywords: Inheritance Law Reform, Institutional Ijtihād, Obligatory Will (Waṣiyyah Wājibah)